2016
DOI: 10.1371/journal.pone.0147489
|View full text |Cite
|
Sign up to set email alerts
|

CLCA2 Interactor EVA1 Is Required for Mammary Epithelial Cell Differentiation

Abstract: CLCA2 is a p53-, p63-inducible transmembrane protein that is frequently downregulated in breast cancer. It is induced during differentiation of human mammary epithelial cells, and its knockdown causes epithelial-to-mesenchymal transition (EMT). To determine how CLCA2 promotes epithelial differentiation, we searched for interactors using membrane dihybrid screening. We discovered a strong interaction with the cell junctional protein EVA1 (Epithelial V-like Antigen 1) and confirmed it by co-immunoprecipitation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 56 publications
3
44
1
1
Order By: Relevance
“…It is in accordance with the findings of others, and therefore tempting to speculate, that downregulation of mCLCA5 in the presence of cells expressing Stat3 activity reflects an invasive phenotype in these cells and potential epithelial–mesenchymal transition. 16, 22, 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is in accordance with the findings of others, and therefore tempting to speculate, that downregulation of mCLCA5 in the presence of cells expressing Stat3 activity reflects an invasive phenotype in these cells and potential epithelial–mesenchymal transition. 16, 22, 24 …”
Section: Discussionmentioning
confidence: 99%
“…CLCA proteins have been associated with diverse functions including cell adhesion, 16 apoptosis, tumourigenesis and mucus cell differentiation. 17 Of particular interest, both CLCA2 and CLCA4 have been shown to inhibit proliferation of breast cancer cells when ectopically expressed in vitro , 18 whereas normal breast tissue exhibits high levels of CLCA2 in both acini and small ducts.…”
mentioning
confidence: 99%
“…CTBP1 plasmid and its control (pcDNA3) were described previously . pGL4 plasmids with different lengths of the CLCA2 promoter, pGIPZ.shCLCA2 and pGIPZ control, pLEX‐CLCA2 and pLEX were described previously …”
Section: Methodsmentioning
confidence: 99%
“…Previously, Elble group showed that CLCA2 is a negative regulator of proliferation and epithelial–mesenchymal transition (EMT) in breast cancer (BrCa) . Recently, they reported that CLCA2 is part of two functional adhesion complexes, one with epithelial V‐like antigen 1 (EVA1) and zona occludens 1 (ZO‐1), and the other with β‐catenin (CTNNB1), that are involved in EMT suppression . Also BrCa patients with low CLCA2 expression in primary tumors have more metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of CLCA2 or CLCA4 is sufficient in HMLE cells to induce the expression of the mesenchymal marker vimentin and supress the epithelial marker E-Cadherin (Walia et al 2012, Yu et al 2013). In the case of CLCA2, the regulation of EMT may at least in part be through interactions with the cell junctional protein EVA1 (Ramena et al 2016). Future studies are now required to define the relative importance in changes in chloride flux in these events, and the ability of the loss of CLCA2 or CLCA4 to induce a mesenchymal phenotype in other models of EMT, including those not of breast cancer origin.…”
Section: Chloride Channels and Emt In Cancer Cellsmentioning
confidence: 99%